Carbo‐Naphthalene: A Polycyclic carbo‐Benzenoid Fragment of α‐Graphyne. (2nd November 2016) - Cocq, Kévin; Saffon‐Merceron, Nathalie; Coppel, Yannick; Poidevin, Corentin; Maraval, Valérie; Chauvin, Remi
Abstract: A ring carbo ‐mer of naphthalene, C32 Ar8 (Ar= p ‐ n ‐pentylphenyl), has been obtained as a stable blue chromophore, after a 19‐step synthetic route involving methods inspired from those used in the synthesis of carbo ‐benzenes, or specifically devised for the present target, like a double Sonogashira‐type coupling reaction. The last step is a SnCl2 /HCl‐mediated reduction of a decaoxy‐ carbo ‐decalin, which is prepared through successive [8+10] macrocyclization steps. Two carbo ‐benzene references are also described, C18 Ar6 and o ‐C18 Ar4 (C≡C‐Si i Pr3 )2 . The carbo ‐naphthalene bicycle is locally aromatic according to structural and magnetic criteria, as revealed by strong diatropic ring current effects on the deshielding of 1 H nuclei of the Ar groups and on the negative value of the DFT‐calculated NICS at the center of the C18 rings (−12.8 ppm). The stability and aromaticity of this smallest fused molecular fragment of α‐graphyne allows prediction of the same properties for the carbon allotrope itself.